Biennial wormwood (Artemisia biennis) competition with soybean (Glycine max) - Nelson, Eric; Kegode, George (Phytoprotection, 2005)
Biennial wormwood has become a serious weed of several crops in the northern Great Plains of the United States and Prairie Provinces of Canada. Greenhouse replacement series experiments were conducted to investigate the effects of watering regime (stressed and non-stressed) and nitrogen rate (50, 100, 150, and 200 mg kg-1 of soil) on competition between soybean and biennial wormwood. Soybean height was reduced after 9 weeks of competition with biennial wormwood compared with soybean grown in monoculture, whereas biennial wormwood plants were taller when grown with soybean than in monoculture. The change in plant height indicated that biennial wormwood height was increased due to interspecific competition, whereas soybean height was reduced. When moisture was limited, the relative yield of biennial wormwood was greater than that of soybean, indicating that biennial wormwood was more aggressive than soybean. Soybean growth was unaffected by an increase in nitrogen rate, whereas biennial wormwood fresh weight was 30% greater when the nitrogen rate was increased from 50 to 200 mg kg-1. Biennial wormwood aggressivity tended to increase as the nitrogen rate was increased from 50 to 200 mg kg-1. Overall results suggest that the negative impact of biennial wormwood competition with soybeans under field conditions may increase when soil moisture is limited and nitrogen fertility is increased.